Study on Mechanical Properties of Flax Fibre Textile Reinforced Composites Fabricated Using Bio-Based Epoxy Resin Matrix - Mahendran, Arunjunai Raj; Wuzella, Gunter; Pichler, Stefan; Lammer, Herfried (Journal of Composites and Biodegradable Polymers, 2014)
Flax fibre reinforced composites were made from non-crimp and woven flax fabric reinforcements using bio-based epoxy resin matrix. The fabrics impregnated with epoxy resin containing 55% biomass carbon were fabricated using vacuum bag technique. The fibre weight content of around 40 wt% was achieved through the vacuum bag technique. The fibre assembly and the morphology of the composites were studied using optical microscope. The influences of different weave type and fibre layup direction on the mechanical properties of composites were studied. It was found that, the woven fabric had lower impact strength values than the unidirectional and biaxial oriented fibres. But the woven fabric had achieved relatively equal impact energies on both directions. The maximum flexural strength (196 MPa) and modulus (13.5 GPa) was observed for the unidirectional non-crimp fabric on 0° fibre layup direction.